2020
DOI: 10.3390/cancers12020510
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Characterization of Non-Invasive Differentiated-Type Gastric Cancer in the Japanese Population

Abstract: Background and aims: Recent genomic characterization of gastric cancer (GC) by sequencing has revealed a large number of cancer-related genes. Research to characterize the genomic landscape of cancer has focused on established invasive cancer to develop biomarkers for therapeutic or diagnostic targets, and nearly all GC reports have been about advanced GC. The aim of this study is to identify recurrently mutated genes in non-invasive GC and, in particular, the driver mutations that are associated with the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Consistently, LRP1 has been related to the poor prognosis of clear-cell renal cell carcinoma [ 58 ]. In addition, LRP1 mutation plays a key role in the occurrence of gastric cancer [ 59 ]. It has been demonstrated that the tPA-LRP1 pathway is a key switch for regulating the progression of melanoma by affecting the cellular composition and proteolytic makeup of the tumor niche [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, LRP1 has been related to the poor prognosis of clear-cell renal cell carcinoma [ 58 ]. In addition, LRP1 mutation plays a key role in the occurrence of gastric cancer [ 59 ]. It has been demonstrated that the tPA-LRP1 pathway is a key switch for regulating the progression of melanoma by affecting the cellular composition and proteolytic makeup of the tumor niche [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nakamura et al reported that LRP1 mRNA levels in gastric cancer with LRP1 mutations were significantly lower than those in gastric cancer without LRP1 mutations. Furthermore, CagA accumulation is significantly increased in gastric cancer tissues with LRP1 mutations [21]. Polymorphisms of LRP1 may be associated with CagA accumulation and atrophic gastritis.…”
Section: Table 4 (Continued)mentioning
confidence: 99%
“…Subsequently, autophagy degrades CagA. However, CAPZA1, a host protein, binds to the LRP1-ICD and inhibits LRP1-induced autophagy cancer [21]. Furthermore, Tsugawa et al reported that CAPZA1 overexpression reduced CagA degradation [20].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, autophagy conversely reduces the intracellular VacA [ 12 ]. Focusing on the relationship between CagA and autophagy, the host’s autophagy degrades the CagA as a host defense mechanism [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%